The role of written corrective feedback in developing writing in L2 - Nagode, Gabrijela (ELOPE (Ljubljana), 2014)
Feedback plays an important role in developing L2 writing in young learners. The article provides a brief overview of the history of giving feedback and of some contemporary views within this field. Special attention is paid to cognitive perspectives, such as the influence of written corrective feedback on shortterm memory, the influence of focused and unfocused written corrective feedback on error correction, the influence of written corrective feedback on a particular category of error, the influence of direct and indirect written corrective feedback and combinations of various types of written corrective feedback, and the influence of educational background and L2 learning background on the effectiveness of written corrective feedback in terms of sociocultural perspectives. The main aim of the article is to present readers (especially teachers) with the variety of aspects of giving written corrective feedback in developing L2 writing and thus in enabling young learners to develop their L2 writing skills more effectively.
Keywords: child; dodatni jezik; mlajši učenci; otroci; pisanje; pisna spretnost; povratne informacije; writing